Analysis of the Use of Dynamic Fluid Learning Media - Dhanil, Muhammad; Afriani Putri, Fina; Desnita, Desnita; Usmeldi, Usmeldi (Physics Education Research Journal, 2024)
Advances in ICT technology support by presenting various forms of innovative media. This study aimed to obtain a profile of schools' most widely used learning media. This research method was quantitative, using surveys to collect data. The respondents of this study were 1095 students from six schools. Questionnaire instruments were used to collect data for students with the help of Google Forms. The results showed that the learning media widely used by smartphones was 14%, PhET was 23%, PowerPoint Was 18%, computers were 17%, and others consisted of flip PDF and video were 28%. Media use in dominance is carried out directly in the classroom in the learning process. This study's findings indicate that using smartphones as a learning medium still needs to be improved. Therefore, these results allow researchers to develop learning media that utilize smartphones, especially in fluid learning materials.